The Poles - Ley, Willy; Editors of TIME-LIFE BOOKS (Time-Life Books : Hong Kong, 1980)
A richly illustrated exploration of the Earth$1 (Bs polar regions, covering: Polar geography and climate Arctic & Antarctic ecology and wildlife History of exploration, including expeditions Glaciology, ice phenomena, and human impact Designed for general readers and enthusiasts of nature and exploration.s
Keywords: Wildlife & geography